La percezione antica dell'Orientalizzante (Aristonothos. Rivista di Studi sul Mediterraneo Antico, 2009)
This article analyzes the perceptions that the ancients had about two key objects of the Orientalizing period, the throne and the crater, considering literary traditions, both contemporary (Homer and the first lyric poets) and later (Atheneus of Naukratis, who quotes Dioscoris and Philochorus, Herodotus, Duris of Samos,…), as well as archaeological finds coming also from Etruscan and Latial areas (e.g. Nestor’s Cup). Both these objects characterized the royal, or at least princely, banquet (daís), until the middle VII century B.C., when the substitution of the usage of the throne (klismoi or thronoi, the latter already present in Mycenaean tablets) with that of the couch (kline) testifies to social evolution. The kline is just one of the ritual elements which differentiates daís (banquet) and symposion. If then, in the case of the throne and of related convivial habits it is possible to envisage an innovation from the Oriental world, datable with sufficient precision but diffused unevenly  (e.g. Crete). In the case of the kratér or depas we can identify a continuity in usage as ritual gift (e.g. Sidonians’ bowl), votive offerings (e.g. Lydian kings’ craters) or reuse (sometimes with deceptive goals, as done by King Pausanias in Platea and Byzantium). Such an usage demonstrates how the awareness of the social preciousness of the apparatus described in these pages was crucial for its acceptance and utilization until the time of the Hellenistic courts.